Navigational entanglements - Bodard, Aliette de (A Tordotcom Book, published by Tom Doherty Associates/Tor Publishing Group, 2024)
"Jockeying navigator clans guide spaceships through the Hollows: an area of space populated by the mysterious but deadly creatures known as Tanglers. When a Tangler escapes the Hollows for the first time in living memory, each clan must send a representative to help capture it--but the mission may be doomed and the hearts of two clan juniors may be in danger too. Viet Nhi is not good with people. Or politics. Which is a problem when the Rooster clan sends her on the mission against her will, forcing her to work with an ill-matched group of squabbling teammates from rival clans, including one who she can't avoid, and maybe doesn't want to. Hac Cúc of the Snake clan has always been better at poisoning and stabbing than at making friends, but she's drawn to Nhi's perceptiveness and obliviousness to social conventions--including the ones that really should make Nhi think twice about spending time with her. But when their imperial envoy and nominal leader is poisoned, this crew of expendable apprentices will have to learn to work together--fast-before the invisible Tangler can wreak havoc on a civilian city and destroy the fragile reputation of the clans. Along the way, Nhi and Hac Cúc will have to learn the hardest lesson of all: to see past their own misconceptions and learn to trust their growing feelings for each other"--